(untitled) (International Journal of Engineering and Computer Science, 2015)
Multiple-input multiple-output (MIMO) systems are today regarded as one of the most promising research areas of wireless communications. This is due to the fact that a MIMO channel can offer a significant capacity gain over a traditional single-input singleoutput (SISO) channel. Bandwidth is one important constraint in wireless communication. In wireless communication, high data transmission rates are essential for the services like triple play i.e. data, voice and video. At user end the capacity determines the quality of the communication systems. This paper aims to compare the different RF wireless communication systems like SISO, MISO, SIMO and MIMO systems on the capacity basis. Ergodic capacity and Outage capacity has also been discussed. Moreover, a computer simulation with Matlab is implemented